Transformative horizons: reflecting on a decade of scenario-guided policy formulation - Vervoort, Joost M.; Pereira, Laura; Veeger, Marieke; Rutting, Lucas; Peou, Rathana; Muzammil, Maliha; Muiderman, Karlijn; Thornton, Philip K.; Cramer, Laura K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Participatory foresight has proliferated rapidly in response to unprecedented global uncertainty and the need to transform to more sustainable societies. However, the link from foresight to action is often under-researched; and understanding how foresight can be used for the realization of transformative ambitions has proven particularly difficult. In this paper, we reflect on a unique case: a project that spans eleven years of scenario-guided participatory policy formulation processes for food security and agriculture under climate change across seven global regions. Many of the policy formulation processes in these regions have led to changed policies and plans as a result of participatory scenario analysis. The length, scope, and level of policy engagement that characterizes this case offers unique opportunities for learning about impactful foresight. In addition, lessons from the project have proliferated into a range of other initiatives that have often been able to complement the original project strategies with new approaches that have in turn yielded more insights. We provide core insights from the successes and failures in this unique global case for connecting foresight to action by examining interactions between 1) institutional contexts and knowledge systems; 2) relationships with the future; 3) imaginaries; 4) participation cultures; 5) process designs and participants; and 6) futures methodology. We then go on to discuss how such best practices can be ‘scaled deep’; ‘scaled out’; and ‘scaled up’ for transformative change.